HUBUNGAN PAPARAN PESTISIDA DENGAN KEJADIAN GANGGUAN KEPEKAAN KULIT PADA PETANI DI DESA SUMBEREJO KECAMATAN NGABLAK KABUPAEN MAGELANG - Hamidah, Tasya; Sulistyani, Sulistyani; Suhartono, Suhartono (Fakultas Kesehatan Masyarakat, 2018)
The existence of pesticides is now very important for farmers because pesticides are easy to use and have high killing power against pests. However, if used excessively can endanger the health of farmers, one of which is to experience a sense of sensitivity to the threshold of the skin. The occurrence of pesticide contamination through the skin is the most common contamination. The results of a preliminary study showed that 5 out of 10 farmers experienced complaints of tingling, itching and numbness. The purpose of this study was to describe and analyze the factors associated with skin sensitivity disorders on farmers in Sumberejo Village, Ngablak Sub-District Magelang District. This type of study was analytic observational with cross sectional approach. Population in this study were 110 farmers. The sample of this study was taken by purposive sampling and the sample size were 43 farmers. Chi Square test results showed that the variabel working period (p value = 0.029), the use of PPE (p = 0.04), and personal hygiene (p value = 0.001) associated with skin sensitivity disorders in farmers. While the variabel working duration (p value = 0.410), number of types of pesticides (p = 0.274), and spraying frequency (p value = 0,453) were not associated with skin sensitivity disorders. There were 24 farmers who skin sensitivity disorder. The conclusion of this study is that the working period, PPE, personal hygiene, and cholinesterase are factors related to skin sensitivity disorders that need to be improved in terms of the use of complete PPE by farmers when spraying.